Winston Cup Preview - (:unkn) unknown (Coy C. Carpenter Library, 1992)
Published in: Synapse. July 1992.
Dr. Jimmy Simon (L), professor and chairman of the Department of Pediatrics, and Gerald Finley (R), vice president for Patient Care Services at North Carolina Baptist Hospital, are holding a check. The amount of money raised was $206,792 by the NASCAR Winston Cup Teams and went towards funding for North Carolina Baptist Hospital's Brenner Children's Hospital and AirCare.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth